Mesenchymal Stromal Cell-Derived Tailored Exosomes Treat Bacteria-Associated Diabetes Foot Ulcers: A Customized Approach From Bench to Bed - Raghav, Alok; Tripathi, Prashant; Mishra, Brijesh Kumar; Jeong, Goo-Bo; Banday, Shahid; Gautam, Kirti Amresh; Mateen, Qazi Noorul; Singh, Prem; Singh, Manish; Singla, Akhil; Ahmad, Jamal (Frontiers in Microbiology, 2021)
Exosomes are nano-vesicles of endosomal origin inherited with characteristics of drug delivery and cargo loading. Exosomes offer a diverse range of opportunities that can be exploited in the treatment of various diseases post functionalization. This membrane engineering is recently being used in the management of bacteria associated diabetic foot ulcers (DFUs). Diabetes mellitus (DM) is among the most crippling disease of society with a large share of its imposing economic burden. DM in a chronic state is associated with the development of micro and macrovascular complications. DFU is among the diabetic microvascular complications with the consequent occurrence of diabetic peripheral neuropathy. Mesenchymal stromal cells (MSCs) derived exosomes post tailoring hold promise to accelerate the diabetic wound repair in diabetic foot ulcer (DFU) associated with bacterial inhabitant. These exosomes promote the anti-bacterial properties with regenerative activity by loading bioactive molecules like growth factors, nucleic acids, proteins and non-bioactive substances like antibiotics. Functionalization of MSCs derived exosomes is mediated by various physical, chemical and biological processes that effectively load the desired cargo into the exosomes for targeted delivery at specific bacterial diabetic foot ulcers and wound. The present study focused on the application of the cargo loaded exosomes in the treatment of DFU and also emphasizes the different approach for loading the desired cargo/drugs inside exosomes. However, more studies and clinical trials are needed in the domain to explore this membrane engineering.